Técnicas de patrones en pantalón de damas y su incidencia en la enseñanza-aprendizaje de corte y confección a estudiantes del bachillerato de la unidad educativa Ana Paredes de Alfaro en el cantón Guayaquil, provincia del Guayas - Ashqui Ati, Martha Cecilia (2017)
Learning arises from the process of exchange, thoughts, opinions and knowledge. The problem was developed in the Ana Paredes educational unit of Alfaro, where a considerable number of students have been seen who have difficulties in the elaboration of ladies ' trousers, which affects the academic and labor competencies. The purpose of this research was focused on analyzing the incidence of pattern techniques in ladies ' trousers. The methodology used consisted of the qualitative and quantitative paradigm, the modality of field, bibliography and feasible project, descriptive, exploratory and bibliographic type that was used to study the cause and effect of the study variables. Non-probabilistic or intentional sampling, was selected by the researcher to study the group where the problem arises, had as results to: 2 managers, 4 teachers and 50 students. The survey said that the majority of students in the area of cutting and dressmaking should improve their overall performance, due to the low level of performance, participation and school undertaking, resulting from the lack of application of patterning techniques in trousers Lady. Finally, the need for the design of a didactic guide that favored the acquisition of learning and improvement of school performance was determined. To carry out this proposal, the problem was detected, examining the specific needs of each student and the resources that enable the application of the Guide, as an instrument of educational support